Batik Industry Wastewater Treatment using Constructed Wetland in Sidoarjo Regency - Soeprijanto, Soeprijanto; Anara, Siti Alicia; Azis, Ahmad Rifky (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2023)
Batik is one of the industrial potentials of Indonesia, which is experiencing rapid growth in various regions. Besides providing economic benefits, the batik industry also harms the environment. One of the processing methods that can be used as a solution is the Constructed Wetland (CW) method. This method is appropriate because it doesn't require high processing and maintenance costs and the process is simple and uses local resources. The purpose of this study was to measure the efficiency of batik industry wastewater treatment in reducing the pollutant load with the CW system so that the waste discharged into the environment can be declared safe. The parameters studied were COD, and TSS with the Hydraulic Retention Time for 10, 20, and 30 days. The results of the analysis of the initial content obtained a COD value of 1832,02 mg/L and a TSS value of 300 mg/L. Based on the results of the research that has been done, the results obtained for the removal of COD and TSS at 10 days HRT were 92.698% and 83.33%, then HRT 20 days of 94.603% and 86.67%. and then HRT 30 days of 96.138 % and 93.33%.